2013
DOI: 10.5101/nml.v5i4.p274-280
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Exchange of Colloidal ZnO Nanocrystals from the High Temperature and Nonaqueous Approach

Abstract: Abstract:Colloidal zinc oxide (ZnO) nanocrystals generated from the high temperature and nonaqueous approache are attractive for use in solution-processed electrical and optoelectronic devices. However, the asprepared colloidal ZnO nanocrystals by this approach are generally capped by ligands with long alkyl-chains, which is disadvantage for solution-processed devices due to hindering charge transport. Here we demonstrate an effective ligand exchange process for the colloidal ZnO nanocrystals from the high tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…XRD patterns (Fig. 1 b) for different thicknesses of ZnO films indicate that the crystallinity with wurtzite structure could be enhanced as the thickness increased [ 15 , 36 ]. Moreover, the c -axis oriented (002) intensity of thicker ZnO film is stronger than the thinner ones, demonstrating the orientation growth which may improve the carrier transport mobility [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…XRD patterns (Fig. 1 b) for different thicknesses of ZnO films indicate that the crystallinity with wurtzite structure could be enhanced as the thickness increased [ 15 , 36 ]. Moreover, the c -axis oriented (002) intensity of thicker ZnO film is stronger than the thinner ones, demonstrating the orientation growth which may improve the carrier transport mobility [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the window layer attracts less attention in spit that it plays the key roles in extracting and transporting charge carriers in heterojunction. As an n-type window layer, ZnO is an ideal candidate due to its relatively high electron mobility, environment stability, and high transparency [ 15 ]. Even utilizing the same window layer of ZnO, different groups utilized varied thickness and obtained over 8% conversion efficiency [ 12 , 14 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Solution-based chemistry techniques can leave insulating surface chemistries on the nanoparticle that can be time consuming to remove before device integration. This is important because ligands can interfere with optoelectronic device performance and efficiency by inhibiting charge transport and preventing the close-packing of particles [ 51 , 52 ]. Additionally, PLFL offers a method to produce bimodal size distributions, further enhancing particle packing which can improve performance [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has already been demonstrated that ZnO is an excellent candidate as an electron-transport layer because it possesses relatively high mobility, high optical transparency (wide band gap), abundance, and ease of fabrication and processing. 18,19 The excellent photosensitive response of ZnO to ultraviolet (UV) radiation is also well-known and adds to its utility in solar cells. 20 Several groups have explored various modifications to ZnO films and monitored the effect of these modifications in solar cells to achieve >8% PCE.…”
Section: ■ Introductionmentioning
confidence: 99%